First records of Pseudocerotidae (Platyhelminthes: Polycladida: Cotylea) from Patagonia, Argentina - Brusa, Francisco; Damborenea, Cristina; Quiroga, Sigmer (Zootaxa, 2009)
In this work we record two species belonging to the polyclad family Pseudocerotidae from the littoral zone of the Península Valdés (Patagonia, Argentina). This is the first record of members of Cotylea and the third of Polycladida from Argentina. The two new records are Phrikoceros mopsus, a species described for Brazil and Colombia and Thysanozoon brocchii, a cosmopolitan species. Morphological features of both species are presented. These two new records contribute to the knowledge of polyclads from Patagonia and to the general understanding of their biogeography in the Southwest Atlantic Ocean.